Response to unfairness across the suicide risk spectrum. (December 2017) - Carbajal, Jessica M.; Gamboa, Jorge L.; Moore, Jordan; Smith, Favrin; Ann Eads, Lou; Clothier, Jeffrey L.; Cáceda, Ricardo
Abstract: Suicidal behavior is frequently triggered by social crises, such as familial, romantic, social or work-related conflict. A variety of cognitive and social functioning impairments has been associated with suicidal thoughts and acts. One of the precipitating and perpetuating factors of social conflict is the desire for retribution after a perceived offense, even at one's own detriment. We utilized the Ultimatum Game—a behavioral economic task which examines the behavioral response to perceived unfairness—in order to characterize the response to unfairness across the acute suicide risk spectrum. We examined five groups of adult individuals of both genders (n = 204): High- and Low-Lethality recent Suicide Attempters, Suicidal Ideators, Non-Suicidal Depressed Patients; and Healthy Controls. We also measured demographic and clinical variables. Even though all depressed groups showed similar rejection rates in the Ultimatum Game, there was a higher likelihood of rejecting offers in the low stakes condition in all acutely suicidal groups compared with healthy controls. Stake size, offer, education, and gender of the proposer were significantly associated with rejection rates. Acutely suicidal patients may be more vulnerable to adverse interpersonal interactions. Further characterization of social behavior may provide targets for secondary and tertiary prevention for high-risk individuals. Highlights: We characterized response to perceived unfairness across suicidality spectrum. We used the Ultimatum Game in a range of suicidal depressed patients and controls. Suicide Attempters and Ideators had likelihood of rejecting offers. Stake size, offer and proposer gender were associated with rejection rates. High lethality attempters may be more vulnerable to adverse social interactions.